Les outils-transducteurs dans les traductions du designer - Claire Azéma (Appareil)
Our bias is to consider translation in design, as the first translation in the languages of things, as defined by Walter Benjamin in On language. In the light of Tim Ingold’s anthropology and the philosophies of Gilbert Simondon and John Dewey, we suggest defining this translation more precisely as a transduction which allows the transfer of a signal from one medium to another and which ensures throughout the correspondence between the manufacturer and the material, a gain for the individual and the environment. Our reflection is based on the project to develop the lapidary museum of the Abbey of Sauve Majeur, in Gironde, carried out by students of the design license to exemplify our argument. Finally, we are developing a reflection on the place of tools as translation transducers in order to arrive at the idea that the designer is in charge of translating human activity into matter, in the process of translation specific to design.